Avaliação de cicatrização de feridas superficiais e profundas, após utilização de curtaivos hemostáticos, em codornas (Coturnix coturnix japonica) - Chiquito, Tainá Maria Pereira (2019)
The adoption of hemostatic powders and propolis-based preparations has become increasingly common to control bleeding and assist in healing. The objective of the work was to evaluate two hemostatic methods, one based on propolis (Alveolex®) and the other on ferric subsulfate powder, after experimental injury in quails. The experiment included 36 quails, which were separated into three groups: control, propolis-based hemostatic and another ferric subsulfate-based hemostatic group, subdivided into two types of wounds, superficial wounds (skin and subcutaneous) and deep wounds that affected skin, subcutaneous and musculature. In the blood test, the hematocrit tended to decrease on the second day of collection, while fibrinogen and leukocytes tended to increase on the second day. The visual evaluation of wound healing showed that the birds submitted to the hemostatic with ferric subsulfate base had delayed healing with formation of crust and distancing of the edges, while in the birds submitted to the hemostatic the propolis base presented healing close to what was expected. In the histological examination, it was possible to observe the presence of chronic inflammation in the tissues of the three groups, with no statistical difference. During the surgical procedure, both hemostatic products controlled the bleeding, but Alveolex® was more efficient, quick to manipulate and without causing damage to the healing process.